2001
DOI: 10.1677/joe.0.1690511
|View full text |Cite
|
Sign up to set email alerts
|

Opioidergic inhibition of luteinising hormone and prolactin release changes during pregnancy in pony mares

Abstract: In equine species, luteinising hormone (LH) and prolactin (PRL) release are reduced throughout pregnancy but increase at foaling. The present experiments were designed to study a possible opioidergic regulation of LH and PRL release in pregnant Shetland mares (n=6). At various stages of pregnancy (days 26·4 0·6, 75·4 5·4, 171·8 2·4, 226·2 4·8, 282·7 3·4 and 319·8 2·1), mares were injected with the opioid antagonist naloxone (0·5 mg/kg body weight) and saline. The two treatments were always separated by 2 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Furthermore, although not evaluated in this study, a potential negative energy balance due to the expected high milk yield in the postpartum crossbred draft mares may have contributed, at least in part, to the inhibition of GnRH and gonadotropins. However, an inhibitory effect of endogenous opioids on GnRH release has not been observed after parturition in mares (Aurich et al, 2001). Another novel finding of the present study is the confirmation in the PP Lactating group (also observed in N-PP Cycling group) of the temporal relationship between FSH and LH, with the…”
Section: Gonadotropins Before Ovulationsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, although not evaluated in this study, a potential negative energy balance due to the expected high milk yield in the postpartum crossbred draft mares may have contributed, at least in part, to the inhibition of GnRH and gonadotropins. However, an inhibitory effect of endogenous opioids on GnRH release has not been observed after parturition in mares (Aurich et al, 2001). Another novel finding of the present study is the confirmation in the PP Lactating group (also observed in N-PP Cycling group) of the temporal relationship between FSH and LH, with the…”
Section: Gonadotropins Before Ovulationsupporting
confidence: 71%
“…In mares, the mean levels of gonadotropins are basal during almost the whole gestation period (Aurich et al, 2001;Ginther, 1992). Periodic FSH surges continue to occur mainly until the first 60 days of gestation; consequently, FSH reaches basal levels after 150 days, has a posterior resurgence 5 days before parturition, and continues to increase until 1 day before or at the parturition day, probably due to several hormonal changes that initiate the foaling process (Ginther, 1992).…”
Section: Gonadotropins Before Ovulationmentioning
confidence: 99%
“…In this study, the ovulation took place at the end of autumn, when PRL decreases to undetectable levels, in non-pregnant mares (Guillaume 2001). Aurich et al (2001) report a nadir of prolactin concentrations on days 172 and 226 of gestation, and a significant increase at the end of gestation. In equine embryo transfer, the major difficulty is the synchrony of the time of ovulation between the donor and recipient mares.…”
Section: Introductionmentioning
confidence: 92%
“…In horses, gestagen concentration at parturition is still at about 50% of the peak level (Nagel et al, 2012;Legacki et al, 2016a), even though the placenta seems to selectively repress gestagen synthesis near term (Legacki et al, 2018). As an ungulate species the newborn foal requires immediate colostrum uptake after birth, and instead of the absolute concentration of both gestagens and E2, the changing ratio of their concentrations mainly based on a steep increase of E2 is assumed to be the most important trigger of lactogenesis (Aurich et al, 2001). In contrast to sheep and assumedly horses, primates including human cannot change the pathway of placental steroid synthesis from P4 to E2 (Figure 1).…”
Section: Gestagens Stimulate Mammogenesis and Inhibit Lactogenesismentioning
confidence: 99%
“…In sows, PRL additionally stimulates the proliferation and development of mammary parenchyma, which requires elevated PRL already during the last trimester of pregnancy (Farmer et al, 2000;Farmer and Quesnel, 2020). Based on Aurich et al (2001) PRL in horses remains elevated until two weeks postpartum. In contrast to other species, PRL levels in cats and dogs remain elevated throughout the entire lactation (Concannon et al, 1978;Banks et al, 1983).…”
Section: The Role Of Prolactin During Lactogenesismentioning
confidence: 99%